Experimental and simulation study on steam gasification of phoenix-dactylifera date palm seeds - Babiker, M.E. (Universiti Malaysia Pahang, 2016)
To predict the performance of a fluidized bed gasifier (FBG) using date palm seeds (DPSs) as feedstock, a two-phase model was developed. The model simulates the hydrodynamic, kinetic reaction and steady state operations using the Aspen plus software. Experimental works were performed to study the effect of bed temperature, steam to biomass ratio, gas yield and carbon conversion efficiency. Six varieties of date palm seeds were studied: Deglet Nour (DN), Piarom (PI), Safawi (SA), Mabroom (MA), Suffry (SU), and Aliya (AL). The experimental data was used to validate the prediction model. Materials, process energy balances along with the minimization of free energy method were considered to measure the gas mole fraction. Different reactors of Aspen simulator, namely RYield, RGibbs and RCSTR plus MATLAB models were used to investigate the behaviour of DPSs in the FBG. The results confirmed that there were significant differences between all DPS varieties and treatments. The simulated results showed a good agreement with the experimental data. The gas yield (13.4 increase), lower heating value (11.9 increase), carbon conversion efficiency (9.7 increase and steam decomposition (17 increase) improved considerably with the rise of temperature from 730°C to 800°C. Higher temperatures under steam gasification boosted the overall efficiency of the gasification process. H2 and CO production increased by as much as 35 and 29 (by volume) respectively at 800°C. CH4 contributed to the total yield of gas by a maximum of 13 and 15 for experimental and simulation works, respectively. CO2, on the other hand, showed a tendency to react positively (more than 50 of the total gas yield) at higher temperatures in both experimental and simulation studies. © Universiti Malaysia Pahang Publishing.